2016
DOI: 10.3390/nu8090527
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Dietary Nutrient Intakes and Hepatic Lipid Contents in NAFLD Patients Quantified by 1H-MRS and Dual-Echo MRI

Abstract: Dietary habits are crucial in the progression of hepatic lipid accumulation and nonalcoholic fatty liver disease (NAFLD). However, there are limited studies using 1H-magnetic resonance spectroscopy (1H-MRS) and dual-echo in-phase and out-phase magnetic resonance spectroscopy imaging (dual-echo MRI) to assess the effects of dietary nutrient intakes on hepatic lipid contents. In the present study, we recruited 36 female adults (NAFLD:control = 19:17) to receive questionnaires and medical examinations, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 39 publications
2
46
0
3
Order By: Relevance
“…A case-control study conducted in 36 Chinese participants also suggested that there is , and BMI e Adjusted for age, sex (only for all participants), BMI, type 2 diabetes, hypertension, hyperlipidaemia, physical activity, educational level, household income, smoking status, drinking status, employment status, energy intake (kcal/d), total carbohydrate intake (g/d), total fat intake (g/d), sweet foods intake (g/d), red meat intake (g/d), white meat intake (g/d), DHA + EPA intake (g/d), and family history of CVD, hypertension, and diabetes no difference in DF intake between NAFLD patients and healthy controls [22]. The mean (standard deviation) intake of DF in cases and control were 21.45 (6.21) and 19.67 (5.47) grams per day [22]. Another study which included 140 Iranians explored the associations between DF intake and NAFLD with adjustments of energy intake, age, and sex [12].…”
Section: Discussionmentioning
confidence: 99%
“…A case-control study conducted in 36 Chinese participants also suggested that there is , and BMI e Adjusted for age, sex (only for all participants), BMI, type 2 diabetes, hypertension, hyperlipidaemia, physical activity, educational level, household income, smoking status, drinking status, employment status, energy intake (kcal/d), total carbohydrate intake (g/d), total fat intake (g/d), sweet foods intake (g/d), red meat intake (g/d), white meat intake (g/d), DHA + EPA intake (g/d), and family history of CVD, hypertension, and diabetes no difference in DF intake between NAFLD patients and healthy controls [22]. The mean (standard deviation) intake of DF in cases and control were 21.45 (6.21) and 19.67 (5.47) grams per day [22]. Another study which included 140 Iranians explored the associations between DF intake and NAFLD with adjustments of energy intake, age, and sex [12].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the protein content of the diet, several studies have reported a significantly higher protein intake in patients with NAFLD compared to controls [ 10 , 39 , 40 , 41 ], while other studies found no difference [ 11 , 45 ]. In 2016, Kobayashi, et al [ 46 ] compared the dietary intake of Japanese patients with NAFLD and T2D.…”
Section: Observations Of Dietary Composition and Patterns In Nafldmentioning
confidence: 99%
“…In a study from Japan, patients with NAFLD had a lower vegetable intake and a higher consumption of fruits and sweets compared to T2D patients [ 46 ]. In 2016, Cheng and colleagues [ 45 ] assessed the relationship between dietary intake and hepatic lipid content in NAFLD, and showed that fiber intake was inversely associated with hepatic fat fraction and intrahepatic lipid.…”
Section: Observations Of Dietary Composition and Patterns In Nafldmentioning
confidence: 99%
“…In these circumstances, a nutritional supplement designed to address the specific metabolic issues associated with the condition may provide unique benefits. A variety of nutritional supplements targeting some aspect of the AUD responses are available or have been proposed [8][9][10][11][12][13][14][15][16][17][18][19][20]. However, none have corrected the disruptions in macronutrient metabolism that lead to hepatic steatosis [11].…”
Section: Introductionmentioning
confidence: 99%